The Effectiveness of Biochar and Compost-Based Fertilizers in Restoring Soil Fertility and Red Chili Yields - Situmeang, Yohanes Parlindungan; Suarta, Made; Sudita, I Dewa Nyoman; Damayanti, Ni Luh Putu Sulis Dewi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
The livestock areas are characterized by vast quantities of animal wastes that can be used as organic manure through composting and biochar production for soil fertility enhancement. This work aims to estimate the potential of increasing soil fertility and red chili production by employing biochar and poschar from different animal wastes. The design used for this study is a factorial pattern and randomized block. The first factor is the type of biochar used, including no biochar, biochar derived from cow manure, biochar derived from goat manure, and biochar derived from chicken manure. The second factor is the type of poschar; this includes poschar derived from cow manure, poschar derived from goat, poschar derived from chicken manure. It can be concluded from the investigation outcomes that applying biochar and poschar substantially affects soil factors such as water content, pH, EC, humic acid, fulvic acid, C, N, P, K, and CEC values. Red chilies increase and yield higher per hectare when various forms of biochar and poschar are applied. The combustion of cow manure and application of biochar products and biochar made from chicken manure produce the highest agronomic performance.